Scenario analysis of alternative management options on the forage production and greenhouse gas emissions in Mediterranean grasslands - Pulina A.; Bellocchi G.; Seddaiu G.; Roggero P.P. (Mountain pastures and livestock farming facing uncertainty: environmental, technical and socio-economic challenges, 2016)
Grazing businesses need to develop an understanding of their greenhouse gas (GHG) budget and be able to assess the impact of alternative management options. In this study annual emissions of the three main agricultural GHGs (CO2, CH4 and N2O) were generated for contrasting management scenarios using 50-year simulations with a biogeochemical model in a sheep-grazing system of Northern Sardinia (Italy). Three stocking rates (0.21, 0.42 and 0.84 LSU ha-1 yr-1) combined with three N fertilization rates (0, 100, 150 kg N ha-1 yr-1) were assessed. CO2 emissions showed higher sensitivity to interannual weather variability than CH4 and N2O emissions, with the system holding its sink capacity but with lower rate of sequestration in the most arid years. When N rates did not exceed 100 kg ha-1, a trade-off can be identified between an adequate pasture production and relatively low GHG emissions. The analysis indicated that there is scope for grazing businesses to choose alternative management options to influence their GHG budget. Studies of this type are challenging for livestock industries and policy makers to work through.
19. Meeting of the FAO-CIHEAM Mountain Pastures Subnetwork, 2016/06/14-16, Zaragoza (Spain)